2017
DOI: 10.1016/j.pec.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Engaging women with an embodied conversational agent to deliver mindfulness and lifestyle recommendations: A feasibility randomized control trial

Abstract: Objective This randomized controlled trial evaluates the feasibility of using an Embodied Conversational Agent (ECA) to teach lifestyle modifications to urban women. Methods Women were randomized to either 1) an ECA (content included: mindfulness, stress management, physical activity, and healthy eating) or 2) patient education sheets mirroring same content plus a meditation CD/MP3 once a day for one month. General outcome measures included: number of stress management techniques used, physical activity leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
137
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 46 publications
3
137
2
Order By: Relevance
“…Those agents are also employed for diverse objectives. Without claiming to be exhaustive, some examples are as follows: Angara et al (2017) present a smart kitchen assistant built on top of IBM Watson for recipe recommendation; Gardiner et al (2017) introduce a conversational agent for awareness creation and behavioural change; Panasiuk et al (2018) On the other hand, building on their user experience expertise, Badiu (2018) claims that today's chatbots are far from being "intelligent", because they guide users through simple linear flows, and their user research shows that users have a hard time whenever they try to deviate from such flows. The authors discusses several characteristics required to improve user experience: the importance of pre-defined buttons and free-text user input, the possibility to follow non-linear flows, the importance of language and tone, the respect of user privacy.…”
Section: Chatbots Intelligent Agents and Conversational Interfacesmentioning
confidence: 99%
“…Those agents are also employed for diverse objectives. Without claiming to be exhaustive, some examples are as follows: Angara et al (2017) present a smart kitchen assistant built on top of IBM Watson for recipe recommendation; Gardiner et al (2017) introduce a conversational agent for awareness creation and behavioural change; Panasiuk et al (2018) On the other hand, building on their user experience expertise, Badiu (2018) claims that today's chatbots are far from being "intelligent", because they guide users through simple linear flows, and their user research shows that users have a hard time whenever they try to deviate from such flows. The authors discusses several characteristics required to improve user experience: the importance of pre-defined buttons and free-text user input, the possibility to follow non-linear flows, the importance of language and tone, the respect of user privacy.…”
Section: Chatbots Intelligent Agents and Conversational Interfacesmentioning
confidence: 99%
“…The VH interface in Figure 2 was mostly delivered via smartphones or personal computers. By tailoring the knowledge base, VH were designed for a range of domains, from managing depression [ 77 ], through end-of-life planning [ 80 ], stress management [ 75 ], and educating about breastfeeding [ 89 ], to preconception care [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 53 articles, 23 explicitly described their VH design process [ 55 , 58 , 59 , 68 , 71 , 73 , 75 , 78 , 80 , 82 - 87 , 89 - 93 , 95 , 97 , 104 ]. The most common design approaches were collaboration with domain experts, qualitative observation of similar human-human interactions, and adoption of public health and governmental guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…In a related study, Gardiner and colleagues [25] assigned 61 women to (1) a condition in which they interacted with a computerized relational agent who provided information on stress management, mindfulness, healthy eating, and physical activity or (2) a control condition in which they met for 60 min with a technician who reviewed education sheets about stress management, mindfulness, healthy eating, and physical activity and were given a CD containing meditation and mindfulness exercises. Results showed that, compared with the control group, women who interacted with the computerized relational agent increased their fruit consumption and decreased their use of alcohol to cope with stress.…”
Section: Electronic Coaches and Relational Agentsmentioning
confidence: 99%